The role of the police and economic order in San Miguel de Tucumán at the end of the XVIII century. Alleged offenders, hoarders and monopolists. - Zamora, Romina Noemí (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper seeks to address the problem of the emergence of role of the police at Río de la Plata, as part of the consequences of enlightened thought at the end of theXVIII century. Special attention is given to the case of the city of San Miguel de Tucumán. The objective of this study is to highlight distinctive elements of the role of the police, as well as the way in which this role was understood by the people of the times: a new disciplinary ield related to establishing proper order and coexistence through a variety of functions and actions. Importance is given to the existing differences between police discourse and that of justice. While justice performed based on the judge’s jurisdictional power, the police, in charge of neighbors and families, justiied their existence through protection,safeguarding the public order based on domestic or economic power. Using the methodology of legal anthropology, an assumption is proposed: the role of the police emerged as a normative ield, closely related to economy, price control, and competition, fostering production and control over the poor. Hence, this study will analyze legal instruments and some of their main application ields.